Studies on the Enhancement of Sparkling Wine and Chocolate Pairing through Compositional Profile Analysis - Camelia Elena Luchian; Elena Cristina Scutarașu; Lucia Cintia Colibaba; Dragoș Grosaru; Valeriu V. Cotea (Foods, 2023)
Consumers are looking to experience as many interesting culinary combinations as possible, and there is a growing tendency to associate wine with various foods. Although there are some studies associating wine with chocolate, especially red wine, no articles have been published referring to sparkling wines. Therefore, the purpose of this investigation was to identify the taste compatibility and sensory synergies between sparkling wine and chocolate, with a focus on identifying combinations that can enhance the tasting experience. For this experiment, 14 variants of sparkling wines obtained in Romania and 5 chocolate assortments were evaluated to identify the best culinary match. White chocolate fitted better with Chardonnay—demi-dry sparkling wine; ruby chocolate presented a good match with Fetească neagră—demi-dry; milk chocolate with 32% cocoa powder associated better with Tămâioasă românească—sweet; and dark chocolate with 70% and 95% cocoa powder had synergic matches with Fetească neagră—sweet. Wine attributes like sweetness, acidity, alcoholic strength and chocolate composition significantly impacted the level of match.